The Effect of Bamboo Charcoal on pH and Hardware in Dailed Well Water - Lensoni Lensoni; T. Karma; Irlan Wilianda (Postgraduate, University of Mataram, 2023)
The problem that is often encountered in clean water is that the quality of the water, both groundwater and river water used by the community, does not meet the requirements of healthy clean water. This study aims to determine the effectiveness of activated charcoal from bamboo on pH and decrease the hardness level of dug well water in the village of Lampoh Keude, Aceh Besar. This study used a Quasi-experimental method, water obtained from residents' wells was processed using the filtration and adsorption method, the filtration media was made using media with a volume of 20 liters which had been modified using sand with a thickness of 10 cm, 10 cm of palm fiber, and 10 gravel cm. The highest pH increase test results occurred in TH III AB media where the resulting pH was 7.7 Â± 0.01 compared to 4.5 before processing. The same thing also happened to a decrease in the hardness level of residents' well water, where the thickness of the charcoal and the length of contact time greatly affected the test results, from the results of the 3 existing media tests, the best results were obtained by TH III AB media with a contact time of 30 minutes where the level The hardness obtained was 279 Â± 3.46 mg/L or a decrease of 47.1% from the initial hardness level of well waste. There is an increase in the pH value of well water after processing, and that the use of bamboo charcoal can also reduce the hardness level of well water